Effectiveness of Labor Inspection Post Job Creation Law in Temanggung Regency - Debrita Arsiyastuti; Rini Werdiningsih (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
This study aims to analyze the effectiveness of labor supervision under the Job Creation Act No. 6 of 2023 in Temanggung Regency, focusing on supervision resources, policy communication, and labor law culture. The study uses a mixed-methods approach with an explanatory sequential design, combining a questionnaire survey of 60 respondents with in-depth interviews with 10 key informants. Quantitative analysis uses descriptive statistics and Pearson Product-Moment correlation, while qualitative data are analyzed using the Miles, Huberman, and Saldaña interactive model. The results show that labor supervision effectiveness is in the low category (mean = 2.37). Supervision resources have a strong positive correlation with supervision effectiveness (r = 0.672; sig. 0.000), followed by labor law culture (r = 0.638; sig.0.000), and policy communication (r = 0.584; sig. 0.000). Centralization of supervision authority to the provincial level post-Job Creation Act has created an authority vacuum at the regency level, weakening inspection reach, wage compliance, and participation in social security. This study recommends strengthening supervisors' capacity, revitalizing vertical communication mechanisms between provinces and regencies, and implementing a community-based legal awareness development program as an integrated intervention strategy.